Artificial intelligence methodologies applied to quality control of the positioning services offered by the Red Andaluza de Posicionamiento (RAP) network - Antonio José Gil; Elena Giménez (International Journal of Interactive Multimedia and Artificial Intelligence, 2012)
On April 26, 2012, Elena Giménez de Ory defend-ed her Ph.D. thesis at University of Jaén, entitled: “Robust methodologies applied to quality control of the positioning services offered by the Red Andaluza de Posicionamiento (RAP) network”. Elena Giménez de Ory defended her dissertation in a publicly open presentation held in the Higher Polytechnic School at the University of Jaén, and was able to comment on every question raised by her thesis committee and the audience. The thesis was supervised by her advisor, Prof. Antonio J. Gil Cruz, and the rest of his thesis committee, Prof. Manuel Sánchez de la Orden, Dr. Antonio Miguel Ruiz Armenteros and Dr. Gracia Rodríguez Caderot. The thesis has been read and approved by his thesis committee, receiving the highest rating. All of them were present at the presentation.